Shaping Ability of 2Shape and WaveOne Gold Files Using Cone-Beam Computed Tomography - Singh, Shalini (J Int Soc Prev Community Dent, 2019)
AIM AND OBJECTIVE: The aim of this study is to evaluate the apical transportation, centering ability, and volume of removed dentin of WaveOne Gold (WOG) and 2Shape with the use of cone-beam computed tomography. MATERIALS AND METHODS: Freshly extracted mandibular teeth with sample size of thirty were carefully chosen and instrumented using the 2Shape and WOG rotary files. Preoperative and postinstrumentation cone-beam computed tomographic scans were done to accomplish mesial and distal dentin walls’ measurements and volume of removed dentin calculations, apical transportation, and centering ratio. Statistical analysis was performed and confirmed by independent t-test. Statistical significance was set at 5%. RESULTS: When shaping ability of 2Shape and WOG was evaluated, it was reported that there was no statistically significant differences noted among the groups in relation to the total volume of removed dentin, apical transportation, and centering ratio. CONCLUSION: It can be concluded that 2Shape and WOG preserved the original canal anatomy well and did not eliminate excess dentin during shaping and cleaning. Rotary nickel–titanium files which work on the principle of rotary movement attained an outcome analogous to that of the rotary files working on reciprocating motion in relation to alteration in angle.